Landfill Leachate as an Additive in Sand-lime Products - Dachowski, Ryszard; Nowek, Milena (Procedia engineering, 2016)
Sand-lime blocks are ecological products. They are produced from natural raw materials: lime, sand and water. Sand-lime elements (also known as silicates) meet ecological requirements both at the production and operation stage. In the process of autoclaving, lime is combined with silica and produces insoluble calcium silicates. Thanks to this process, silicate bricks and blocks are characterized by their high strength and durability. Environmental aspects are of great importance in modern construction. Therefore, attention should be paid to the possibility of the production of silicates from waste materials. This article aims to investigate the possibility of using the leachate from environmental landfills (inert waste, which is not subject to specific physical, chemical or biological alternations) as a modifier of properties of sand-lime products.